ANALYSIS OF FACTORS THAT INFLUENCE THE PROFIT MANAGEMENT DIRECTION IN MANUFACTURING COMPANIES LISTED STOCK EXCHANGE IN INDONESIA - misral misral (Akuntansi & Ekonomika, 2019)
His thesis discusses the influence of factors that influence the direction of earnings management in manufacturing companies listed on the Indonesia Stock Exchange either partially or simultaneously. This research is a quantitative study, that is research based on the philosophy of positivism, used to examine certain populations or samples. The population used in this study is manufacturing companies (industrial sector) which are listed on the Indonesia Stock Exchange in 2018 totaling 58 companies, while the sample in this study is 43 companies with a data period of 3 years namely from 2016 to 2018, so the data will be presented as 129 data. The sampling technique uses purposive sampling method. The results of the study concluded that profitability (X1), leverage (X2) and company size (X3) had a significant effect on earnings management on manufacturing companies listed on the Indonesia Stock Exchange either partially or simultaneously. The results of the study also suggest the company to maximize the increase in profitability and maximize the condition of the company's ability to guarantee the value of its debt so that the value of earnings management can continue to increase.